Petroleum pollution changes microbial diversity and network complexity of soil profile in an oil refinery - Zhuang, Jugui; Zhang, Ruihuan; Zeng, Yufei; Dai, Tianjiao; Ye, Zhencheng; Gao, Qun; Yang, Yunfeng; Guo, Xue; Li, Guanghe; Zhou, Jizhong (Frontiers in Microbiology, 2023)
Petroleum pollution resulting from spills and leakages in oil refinery areas has been a significant environmental concern for decades. Despite this, the effects of petroleum pollutants on soil microbial communities and their potential for pollutant biodegradation still required further investigation. In this study, we collected 75 soil samples from 0-5 m depths of 15 soil profiles in an abandoned refinery to analyze the effect of petroleum pollution on soil microbial diversity, community structure and network co-occurrence patterns. Our results suggested soil microbial α-diversity decreased under high C10-C40 levels, coupled with significant changes in community structure of soil profiles. However, soil microbial network complexity increased with petroleum pollution levels, suggesting more complex microbial potential interactions. A module specific for methane and methyl oxidation was also found under high C10-C40 levels of soil profile, indicating stronger methanotrophic and methylotrophic metabolic activities at the heavily polluted soil profile. The increased network complexity observed may be due to more metabolic pathways and processes, as well as increased microbial interactions during these processes. These findings highlight the importance of considering both microbial diversity and network complexity in assessing the effects of petroleum pollution on soil ecosystems.